The interweaving of popular generic modes and modernist techniques in Nostromo : A tale of the seaboard - Fernández, Silvana Noelí; Montezanti, Miguel Angel (2004)
Nostromo. A Tale of the Seaboard (1904), una de las novelas más experimentales del período modernista temprano, ha sido considerada la obra maestra de Joseph Conrad y su más grande lienzo. Un rasgo particular de la novela es que en ella coexisten la experimentación técnica del modernismo, la altamente difusa ficción del narrador y la situación de narración de historias y el paradigma narrativo de los subgéneros "degradados" de la novela de aventuras, el romance y el melodrama. Este estudio indaga las relaciones que se establecen entre dichos elementos, a todas luces anacrónicos o pertenecientes a espacios culturales diferentes, y se propone mostrar que estas discontinuidades no deben ser consideradas una falla sino índices de una tensión constitutiva de la novela.
Described by Conrad as his largest canvas and often considered his masterwork, Nostromo. A Tale of the Seaboard (1904) is one of the most experimental novels of the early modernist period. Nostromo, brings together elements which, like modernist technical experimentation, the diffuse fiction of the storyteller and the storytelling situation and the narrative paradigm of "degraded" subgenres- adventure stories, romance and melodrama-, seem either anachronistic or typical of two distinct cultural spaces. This study of Nostromo engages theoretically with the discontinuities present in this work. I claim such discontinuities ought not to be dismissed as a fault; rather, they ought to be regarded as symptons laying bare a shaping tension in the novel.
Keywords: Conrad; Nostromo; Géneros populares; Modernismo; Espacios de la cultura; Conrad; Nostromo; Popular genres; Modernism; Spaces of culture